Ethnic conflicts in the former Yugoslavia as a consequence of nation-state building - Beširević, Nataša (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2010)
This paper deals primarily with exploring the connection between the creation of nation states, on the one hand, and, on the other, ethnic cleansing and violence in the former Yugoslavia. It argues that the process of creation of nation states in the former Yugoslavia was an inevitable political process, whereas the ethnic strife, violence and genocide were not a "natural" part of that process. Ethnic intolerance did not increase before the war, but it did dramatically increase during the conflict and this increase provides counter-evidence to theories about ethnic hatred. It was certain political élites who provoked ethnic cleansing, primarily by the manipulation of public images, in order to win or keep power. This argument uses instrumentalism as the theory of ethnic conflicts, but other ethnicity theories are briefly introduced in the first part of the paper as well. The argumentation in the second part is based on an analysis of the creation of nation states and the appearance of nationalism in the Western Balkans. It explains the inescapability of the disintegration of socialist federations and the creation of independent states and through empirical research shows that ethnic hate was not dominant, whereas nationalism was extremely strong and finally became the main alternative to evanescent socialism.
Keywords: Balkan; Balkans; Jugoslavija; Yugoslavia; etnični konflikti; nacionalne države; nationalism; nacionalizem